Research on the Impact of Corona Virus Pandemic to Efficiency Profitability at Several Banks in Indonesia - Prabowo, Riefky (Asosiasi Peneliti Manajemen Adat Indonesia, 2023)
We are faced with millions of problems due to the corona virus pandemic, many industries and daily human activities have changed, there must be differences that exist in order to exist. Banks are one of the financial institutions that have also been affected by the coronavirus pandemic. This study collects secondary data by comparing time series and using several banks from 3 conventional banks and 2 Islamic banks in Indonesia. At the end of this study will provide results on the impact of the corona virus on profitability efficiency by using Logistic Regression to describe some of the relationships presented as a decrease or increase in efficiency profitability and ROA due to the corona virus pandemic in Indonesia, there are several impacts and no impact is produced.